Assessing the Adaptability of Rural Households to Tourism from the Perspective of a Social-ecological System: A Case Study of Two Villages in Beijing Suburbs. Issue 3 (1st September 2018) - Dai, Linlin; Liu, Lun; Cui, Jingjing
Abstract : A framework is established for evaluating the adaptability of rural households to tourism disturbance in the suburbs of a metropolis, based on the theory of the social-ecological system with tourism as the system disturbance. Two traditional villages in Beijing suburbs are selected as study cases and compared in terms of the development stage of tourism and the phases and approaches of adaption by rural households to tourism disturbance. Stepwise regression and grey relational analysis are applied to investigate the factors influencing the functionality and stability of the rural social-ecological system.